Analysis of differences in teacher professionalism in terms of gender and length of service - Septia Irnanda Saputra; Sirajul Munir; Elda Herlina; Abhanda Amra; Jamilus Jamilus (Indonesia Auditing Research Journal, 2026)
professionalism is a key factor in improving the quality of education. However, in practice, there are still discrepancies between empirical findings and normative assumptions regarding the influence of teacher demographic characteristics, particularly gender and tenure, on teacher professionalism. Some studies indicate differences in professionalism based on gender and teaching experience, while others show inconsistent results. This uncertainty raises the need for empirical studies to objectively examine the influence of gender and tenure on teacher professionalism. This study aims to analyze teacher professionalism in terms of gender and tenure, and to examine the interaction between these two variables on teacher professionalism. This study used a quantitative approach with a survey method of 42 teachers. Data were analyzed using the t-test, Two-Way ANOVA, and the nonparametric Mann–Whitney test. Limited interviews were conducted as supporting data to strengthen and clarify the results of the statistical analysis. The results showed that gender and tenure did not significantly influence teacher professionalism, either partially or simultaneously, and there was no significant interaction between gender and tenure on teacher professionalism. These statistical findings were reinforced by interview results, which showed that teachers carry out professional duties based on the same competency standards regardless of gender or tenure. This study concludes that teacher professionalism is more influenced by school systems and culture than by individual demographic characteristics. These findings have implications for competency-based teacher professional development and strengthening teacher development systems in schools.